2019
DOI: 10.1002/cnr2.1218
|View full text |Cite
|
Sign up to set email alerts
|

Chinese‐Australian women with breast cancer call for culturally appropriate information and improved communication with health professionals

Abstract: Background: For culturally and linguistically diverse patients, breast cancer presents complex physical, psychosocial, and health care challenges, often exacerbated by a lack of culturally appropriate information and communication barriers with the treating team (even with the help of interpreters).Aim: This qualitative study aims to broadly explore the experience of breast cancer and coping strategies utilized by Chinese-Australian women.Methods and results: Twenty-four Chinese-Australian women with breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This feedback aligns with previous review findings that treatment-related information is among the most commonly reported unmet information needs (Lim et al, 2017;Wu et al, 2020). Chinese immigrants have reported receiving less information than desired (Levesque et al, 2020;Shaw et al, 2015), or information only being available in English (Kwok & White, 2014). Consequently, lack of access to information combined with limited English-language proficiency can impede informed treatment decision-making (Shaw et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This feedback aligns with previous review findings that treatment-related information is among the most commonly reported unmet information needs (Lim et al, 2017;Wu et al, 2020). Chinese immigrants have reported receiving less information than desired (Levesque et al, 2020;Shaw et al, 2015), or information only being available in English (Kwok & White, 2014). Consequently, lack of access to information combined with limited English-language proficiency can impede informed treatment decision-making (Shaw et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…This may be attributed to doctors spending more time communicating with the interpreter rather than the patient or family member themselves. Consequently, patients and caregivers may not have the opportunity to ask all their questions due to interpreter and clinician time constraints Levesque et al, 2020). Having a QPL may facilitate more direct communication with clinicians, shortening the time needed for an interpreter to generate questions and interpret responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] In addition, Chinese obedience to authority makes women don't dare to ask health professions directly for fear of asking silly questions or being labeled as a "bad patient". [30] Women may prefer health professional to provide clear information without ask to many questions. [31] Therefor, health professions need to discuss the practical, longer-term real-world challenges associated with each of the surgical treatment options with patients.…”
Section: Discussionmentioning
confidence: 99%
“…[28] In addition, Chinese obedience to authority makes women don't dare to ask health professions directly for fear of asking silly questions or being labeled as a "bad patient". [29] Women may prefer health professional to provide clear information without ask to many questions. [30] Therefor, health professions need to discuss the practical, longer-term real-world challenges associated with each of the surgical treatment options with patients.…”
Section: Discussionmentioning
confidence: 99%